Pengaruh Perceived Usefulness, Perceived Ease of Use, Perceived Price, Free Alternatives terhadap Willingness to Subscribe Pengguna Aplikasi - Ahmad Nurhadi; Igo Aldafa Putra; Hapsai Dyah Herdiany; Anindita Iman Basri (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2025)
This study aims to examine Perceived Usefulness, Perceived Ease of Use, Perceived Price and Free Alternatives on Willingness to Subscribe of Vidio Application Users in the Special Region of Yogyakarta. This study will explore how perceptions of application benefits (perceived usefulness), ease of use (perceived ease of use), subscription prices (perceived price), and the availability of free alternatives (free alternatives) can affect user intentions to subscribe. This study will also identify the combined influence of these factors on user decisions. The results of this study are expected to provide insight for Vidio application developers and marketers in designing marketing strategies. This study was conducted in November 2024 - January 2025 in the Special Region of Yogyakarta. The sample used in this study amounted to 100 respondents with the sampling technique used in this study using non-probability sampling technique using the purposive sampling method as a method for sampling with specified criteria. The data analysis technique used was multiple linear regression and hypothesis testing using the t-test and f-test with the help of the SPSS 25 for windows program.